Byzantine Philosophy : A Systematic Perspective - Karpiev, Georgi, (Late Antiquity and Medieval Studies E-Books Online, Collection 2025., 2025)
The book is the result of thirty years of Georgi Kapriev's work in the field of Byzantine philosophy. Contrary to long-held opinions that no authentic philosophy existed in Byzantium, the fullness and complexity of this philosophical tradition are offered. The subject is its context and its main themes, presented in their systematic framework. The areas in which this tradition differs from the Latin tradition and which constitute its contribution are highlighted. Among these are the focus on being as a dynamic network, on teachings on natural and creative activities, on divine logoi and the self-existence of things, and on freedom.